2018
DOI: 10.1007/s11011-018-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways

Abstract: To assess whether EGb761 could protect elderly diabetic mice with cognitive disorders and explore the role of beclin-1-mediated autophagy in these protective effects. Two-month-old male db/db−/− mice and wild-type C57/BL6 mice were randomly divided into six groups: db/db−/− control, db/db−/− 50 mg, db/db−/− 100 mg, wild-type (WT) control, WT 50 mg, and WT 100 mg. EGb761 (50 mg/kg or 100 mg/kg of bodyweight) was given by gavage once a day for 1 month from the age of 6 months. Y-maze and social choice tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Guan et al (2018) during a study on diabetic mice demonstrated that treatment with EGb761 causes improvement of diabetic neurological disorders identified by MRI. The extract also causes normalization of blood pressure and improvement of learning and memory during Y‐maze test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guan et al (2018) during a study on diabetic mice demonstrated that treatment with EGb761 causes improvement of diabetic neurological disorders identified by MRI. The extract also causes normalization of blood pressure and improvement of learning and memory during Y‐maze test.…”
Section: Resultsmentioning
confidence: 99%
“…Beclin‐1 and LC3 genes expression increase in autophagy; so that EGb761 can inhibit autophagy in brain nerve cells. Generally, EGb761 can help to improve neurological disorders in diabetic mice by inhibition of autophagy and inflammation (Guan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The overactivation of autophagy during neuron loss is involved in PD pathogenesis [ 30 ]. According to a new study, Beclin-1 has important functions in autophagy that are mediated by the formation of the Beclin-1-Bcl2 complex [ 31 ]. LC3II is considered a marker of autophagy in cells and tissues [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 A new study has noted that Beclin1 works in autophagy via complexes like the Beclin1-PI3KC3 or Beclin1-Bcl-2 complex. 32 LC3II was considered as an autophagy-linked marker in cell tissues. 33 YAP plays a role in the processes of autophagy and apoptosis 34 and silencing YAP increased the ratio of LC3-I and LC3-II, accompanied by the autophagy-related protein Beclin1.…”
Section: Discussionmentioning
confidence: 99%